Effect of Spirogyra neglecta on the early stages of 1, 2-dimethylhydrazine-induced colon carcinogenesis in rats - Sirinya Taya (2018)
© 2018 Wolters Kluwer Health, Inc. All rights reserved. This study focused on the chemopreventive effects of Spirogyra neglecta extract (SNE) and dried S. neglecta mixed diet on the early stages of 1,2-dimethylhydrazine (DMH)-induced colon carcinogenesis in rats. Male Wistar rats were injected with DMH to initiate aberrant crypt foci (ACF) formation. In the initiation stage, SNE significantly decreased the number of ACF in the colon of DMH-treated rats. Rats that received a low dose of SNE showed enhanced activity of several detoxifying and antioxidant enzymes. In the postinitiation stage, a low dose of SNE significantly decreased the number of ACF in the colon of DMH-treated rats. It significantly reduced the number of proliferating cell nuclear antigen-positive cells and increased the number of apoptotic cells in colonic crypts. S. neglecta thus inhibited the development of the early stages of DMH-induced colon carcinogenesis in rats by modulation of xenobiotic metabolizing enzymes and inhibition of cell proliferation as well as induction of apoptosis.